2023
DOI: 10.3389/fmedt.2023.1195529
|View full text |Cite
|
Sign up to set email alerts
|

Toxic or not toxic? The specifications of the standard ISO 10993-5 are not explicit enough to yield comparable results in the cytotoxicity assessment of an identical medical device

Abstract: BackgroundMedical device manufacturers are obliged to prove the biocompatibility of their products when they come into contact with the human body. The requirements for the biological evaluation of medical devices are specified by the international standard series ISO 10993. Part five of this series describes the performance of in vitro cytotoxicity tests. This test evaluates the effects of medical device use on cell health. The existence of the specific standard suggests that the tests will produce reliable a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The cytotoxicity was assessed in vitro in the porcine kidney epithelial cells LLC-PK1 and Hep G2 human hepatocellular carcinoma cells by the МТТ-test. The reduction of viability of both cell types after incubation with the DIVEMA/PLGA NP or plain PLGA NP in the concentration of up to 100 µg/mL did not exceed 20%, which is generally accepted as the non-toxic effect [29].…”
Section: Resultsmentioning
confidence: 83%
“…The cytotoxicity was assessed in vitro in the porcine kidney epithelial cells LLC-PK1 and Hep G2 human hepatocellular carcinoma cells by the МТТ-test. The reduction of viability of both cell types after incubation with the DIVEMA/PLGA NP or plain PLGA NP in the concentration of up to 100 µg/mL did not exceed 20%, which is generally accepted as the non-toxic effect [29].…”
Section: Resultsmentioning
confidence: 83%
“…Also, cell viability results from monomer exposure have shown to be largely dependent on the cell model systems used [ 41 ]. In addition, interlaboratory tests have shown that the ISO 10993-5 specifications set are not explicit enough to obtain comparable results for a medical device [ 42 ]. In summary, misinterpretations, overshadowing of possible cytotoxic effects, and false conclusions could be the result.…”
Section: Discussionmentioning
confidence: 99%
“…Wound dressings designed for human application necessitate a noncytotoxic nature. Our selection of primary cell lines was guided by their heightened sensitivity to potential cytotoxic agents [ 65 ] than immortalized cell lines and the fact that the utility of using the standard cell line (mouse fibroblast L929) employed for cytotoxic evaluations in the registration of a medical device for cytotoxic evaluation is currently questioned [ 66 ]. Furthermore, mesenchymal stem cells, encompassing the UCSC cells employed in this investigation, exhibit a migratory propensity towards sites of tissue and organ injury, thereby orchestrating and overseeing the regenerative processes therein [ 67 ].…”
Section: Discussionmentioning
confidence: 99%